The Strategies of West Java’s Regional Energy Management To Support National Energy Security - Thamrin, Suyono; Ambarwati, Rita; Hidayat, Syaiful (International Journal of Energy Economics and Policy, 2020)
The focus of this research is to analyze energy potential in West Java Province, and its management. The purpose of this study is to first analyze the energy potential of his particular region in West Java Province; the second one is to analyzes the indicators that affect regional energy security in West Java. This study uses a qualitative method. Data obtained from observations, interviews and literature studies. The results show that West Java has strong potential in contributing to making Indonesia the largest geothermal user in the world. Utilization of geothermal energy for electricity generation in fields that are already in production, can already be said to be optimal. However, there are still several other geothermal resource locations that can still be developed and utilized. Other new renewable energy potentials are the Mini and Micro Hydro potential of 647 MW and a new exploitation of 18.3 MW, Solar Energy with a potential of 9,099 MW but which has only been used up to 0.3 MW, and Bioenergy from the potential of 2,551 MW has only been utilized at 109, 3 MW and several other new renewable energy potentials which are still in the development stage such as Wind Energy and Sea Energy. West Java Provincial energy security indicators are still based on Availability, Affordability, Accessibility, Acceptability, and Sustainability) coupled with: elasticity between economic and electricity growth, energy diversification, and energy conservation. Keywords: Energy Management, Energy Security, Potential Energy JEL Classifications: H56, O13, P48 DOI: https://doi.org/10.32479/ijeep.10259